Unusual bilateral pneumothoraces due to the pleural window acting as a one-way valve - Suzuki, Hirofumi; Nishimura, Motohiro; Okada, Satoru; Inoue, Masayoshi (Journal of Thoracic Disease, 2018)
Simultaneous bilateral spontaneous pneumothoraces are relatively rare and only 1.3% of spontaneous pneumothorax cases are bilateral as well as simultaneous (1). We present a case of simultaneous bilateral pneumothoraces in a patient who followed a complicated course due to a pleuro-pleural communication.